ART of AI governance : Pro-ethical conditions driving ethical AI governance - Niemenmaa, Anttoni (My University, 2021)
In recent years, artificial intelligence has transformed world from agriculture to health care. Alongside even greater opportunities, challenges also rise. Despite its young age, the field of AI ethics has revealed many problems, such as biases and opaqueness of AI systems. Guidelines for ethical AI exist, but a global consensus is yet to be achieved. A gap between ethics and practice is starting to shift focus from abstract ethical constructs towards organizations and practice. Starting point of this thesis is that bottom-up ethics work falls under AI governance, which is another area of active research. AI governance models range from procurement to systematic scale, but organizational models are scarce. Because of its many sides, AI governance in the context of organizations that develop AI also need further defining. This thesis addresses these gaps by focusing on the link between AI governance and AI ethics in organizations developing AI. We develop an AI governance model on the basis of literature utilizing proto-ethical constructs of accountability, transparency and responsibility (ART). This model is then enriched with data gathered from semi-structured interviews of 10 Finnish AI professionals. The purpose is to explain relationships between vendors and customers and highlight possibilities and challenges of implementing practical ethics into AI development process. The findings reveal that ethics currently manifest in AI development, especially in the banking and financial sector. Organizational AI governance offers many avenues to implement, enforce and oversee ethics not just in the development process, but in the organization as a whole. The most remarkable finding is that, while vendor organizations display responsibility in their work, a threat to ethical AI often rises from the customer's side. The interviewees noted that customers do not seem to be interested in paying for ethics, and because of customer's ultimate decision-making power, this can hinder vendors' from giving advice on the ethics of AI. This finding requires further investigation, for which this thesis offers a good starting ground.

Viime vuosina tekoäly on mullistanut maailmaa maataloudesta terveydenhoitoon. Näiden laajojen mahdollisuuksien lomassa kuitenkin ilmenee myös haasteita. Uutuudestaan huolimatta tekoälyetiikan tutkimusala on jo paljastanut useita ongelmia, kuten tekoälyjärjestelmien vääristymiä ja läpinäkymättömyyttä. Suosituksia eettiseen tekoälyyn on olemassa, mutta maailmanlaajuista konsensusta ei ole vielä saavutettu. Kuilu etiikan ja käytännön välillä on alkanut siirtää huomiota abstrakteista määritelmistä tekoälyä kehittäviin organisaatioihin ja käytännön toimiin. Tässä tutkielmassa esitetään, että tämä etiikkatyö on osa tekoälyn hallintoa (AI governance), joka on toinen aktiivinen tutkimusalue. Tekoälyn hallintomalleja on luotu tekoälyä hankkiville organisaatioille, mutta ei juurikaan tekoälyä kehittäville. Tekoälyhallinnon moninaisuuden vuoksi myös kehittäjäorganisaatioita varten tarvitaan tarkempia määritelmiä. Tämä pro gradu -tutkielma pyrkii osaltaan täyttämään näitä aukkoja keskittymällä tekoälyn hallinnon ja tekoälyetiikan väliseen yhteyteen niissä organisaatioissa, jotka kehittävät tekoälyä. Kehitämme tekoälyn hallintomallin kirjallisuuden pohjalta hyödyntäen protoeettisiä vastuun (accountability), läpinäkyvyyden (transparency), ja vastuullisuuden (responsibility) käsitteitä (ART). Tätä mallia täydennetään datalla, joka kerättiin haastattelemalla 10:tä suomalaista tekoälykehityksen ammattilaista. Tarkoituksemme on selittää toimittajan ja tilaajan suhdetta ja löytää niin mahdollisuuksia kuin haasteita käytännön etiikan jalkauttamiseen tekoälyn kehityksessä. Löydökset paljastavat, että etiikka on läsnä nykyisessä tekoälykehityksessä, erityisesti pankki- ja finanssialalla. Organisaation tekoälyhallinto tarjoaa monia mahdollisuuksia eettisen kehityksen implementointiin, vahvistamiseen ja valvontaan ei pelkässä kehitysprosessissa, vaan koko organisaatiossa. Merkittävin löydöksemme oli, että uhka eettiselle tekoälykehitykselle nousee usein tilaajan puolelta, siinä missä toimittajat toimivat usein varsin vastuullisesti. Haastateltavamme totesivat, etteivät tilaajat ole kovin kiinnostuneita maksamaan etiikasta. Koska päätäntävalta on loppujen lopuksi tilaajalla, toimittajan mahdollisuudet ottaa eettiset näkökulmat huomioon ovat rajalliset. Tämä löydös osoittaa jatkotutkimuksen olevan tarpeen, ja tähän tämä tutkielma tarjoaa hyvät lähtökohdat.
Keywords: artificial intelligence, machine learning, AI ethics, AI governance, accountability, transparency, responsibility, semi-structured interviews